Evaluation of the role of peripheral artery plaque geometry and composition on stent performance. (April 2021) - Noble, Christopher; Carlson, Kent D.; Neumann, Erica; Doherty, Sean; Dragomir-Daescu, Dan; Lerman, Amir; Erdemir, Ahmet; Young, Melissa
Abstract: Peripheral stent fracture is a major precursor to restenosis of femoral artery atherosclerosis that has been treated with stent implantation. In this work, we validate a workflow for performing in silico stenting on a patient specific peripheral artery with heterogeneous plaque structure. Six human cadaveric femoral arteries were imaged ex vivo using intravascular ultrasound virtual histology (IVUS-VH) to obtain baseline vessel geometry and plaque structure. The vessels were then stented and the imaging repeated to obtain the stented vessel lumen area. Finite element (FE) models were then constructed using the IVUS-VH images, where the material property constants for each finite element were calculated using the proportions of each plaque component in the element, as identified by the IVUS-VH images. A virtual stent was deployed in each FE model, and the model lumen area was calculated and compared to the experimental lumen area to validate the modeling approach. The model was then used to compare stent performance for heterogeneous and homogeneous artery models, to determine whether plaque geometry or composition had added effects on stent performance. We found that the simulated lumen areas were similar to the corresponding experimental values, despite using generic material constants. Additionally, the heterogeneous and homogeneous lumen areas were also similar, implying that plaque geometry is a stronger predictor of stent expansion performance than plaque composition. Comparing stent stress and strain for heterogeneous and homogeneous models, it was found that stress from these two models had a strong linear correlation, while the strain correlation was weaker but still present. This implies that stent performance may be predicted with a simple homogeneous material models accounting for overall geometry of the plaque, providing that stent fatigue is calculated using stress criteria.